2019
DOI: 10.1093/cid/ciz878
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Telehealth-Based Antimicrobial Stewardship Program in a Community Hospital Health System

Abstract: Background Data on antimicrobial stewardship programs (ASPs) facilitated via telehealth in the community hospital setting are limited. Methods A telehealth-based ASP was implemented in two community hospitals (285 and 176 beds). Local pharmacists without residency or prior antimicrobial stewardship training were trained to conduct prospective audit and feedback. For approximately 60 minutes three times weekly at the 285-bed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…These findings suggest that the active involvement of ID specialists, even if not on-site, can be an effective approach to stewardship. Other smaller non-randomized studies have found that the involvement of remote ID specialists in stewardship activities can reduce antibiotic use [9][10][11]23]. All non-ID sites in our study's cohort reported communicating with off-site ID specialists, but only one of the sites identified an offsite ID specialist as their stewardship champion.…”
Section: Discussionmentioning
confidence: 56%
“…These findings suggest that the active involvement of ID specialists, even if not on-site, can be an effective approach to stewardship. Other smaller non-randomized studies have found that the involvement of remote ID specialists in stewardship activities can reduce antibiotic use [9][10][11]23]. All non-ID sites in our study's cohort reported communicating with off-site ID specialists, but only one of the sites identified an offsite ID specialist as their stewardship champion.…”
Section: Discussionmentioning
confidence: 56%
“…8 For hospitalized patients there are numerous reports of using telehealth for rapid evaluation for intensive care and subspecialty consults such as dermatology, infectious diseases, and psychiatry, where a thorough chart review, history, and visual exam may provide consultants with sufficient information to make clinical recommendations. [9][10][11][12][13][14][15][16][17][18] Telehealth has also been used to engage patients and families in their care during and after hospitalization. [19][20][21] One major limitation to the widespread adoption of telehealth initiatives has been the lack of payment models 22 however, in response to the COVID-19 pandemic both federal and state governments have loosened restrictions on privacy and billing for telehealth visits in an effort to allow health care providers to continue to care for patients while reducing potential exposure to the virus.…”
Section: Background and Significancementioning
confidence: 99%
“…A different remote ASP model described by Shively and colleagues wherein ID physicians provided antimicrobial stewardship services via telehealth to two community hospitals also reported similar acceptance rates (88.9%); however, they found statistically significant reductions in antimicrobial use (342.1 vs. 258.7 DOT/1000 PD, p < 0.001) [12].…”
Section: Discussionmentioning
confidence: 75%